Longitudinal unzipping of 2D transition metal dichalcogenides - Suchithra Padmajan Sasikala (Nature Portfolio, 2020)
Reliable unzipping of the basal plane of mono-elemental graphene and phosphorene has only been reported thus far. Here, the authors demonstrate the unzipping of bi-elemental 2D MX2 transition metal chalcogenides as a general route to synthesize 1D nanoribbon structures.